Treatment of Severe Japanese Encephalitis Complicated With Hashimoto’s Thyroiditis and Guillain-Barré Syndrome With Protein A Immunoadsorption: A Case Report - Zang, Qiuling; Wang, Yating; Guo, Junshuang; Long, Liyang; Zhang, Shuyu; Cui, Can; Song, Dandan; Yu, Boguang; Tang, Fenlan; Teng, Junfang; Miao, Wang (Frontiers in Immunology, 2022)
A severely comatose female patient was diagnosed with Japanese encephalitis (JE). Her condition was complicated by Hashimoto’s thyroiditis (HT) and Guillain-Barré syndrome (GBS). After antiviral, glucocorticoid, and immunoglobulin treatment, the patient’s consciousness was restored, and she could breathe spontaneously. Following this, new-onset, primarily demyelinating GBS developed, which progressed to demyelination combined with axonal injury. The patient was switched to protein A immunoadsorption (PAIA) therapy, and her Hughes score decreased rapidly, from 4 to 1 after 6 months. This patient is the first to receive PAIA combined with an antiviral-glucocorticoid-immunoglobulin regimen to treat encephalitis, meningitis, HT, and GBS caused by JE infection, thereby reflecting the importance of clinical application of PAIA in the treatment of immunological complications of JE.